(untitled) (Kwasu International Journal of Educational Management and Leadership, 2026)
In spite of all governments' efforts to bring overall development to every part of the country, rural communities still lag behind in acquiring some basic amenities but underdeveloped as compared to urban areas. This paper seeks to explore community self-help as a tool for enhancing sustainable community development among rural dwellers in Nigeria. The paper further explained why the rural dwellers need to embrace self-help initiative to make up for neglect and delay on the part of government. It aims to adopt Self-help as a tool for enhancing sustainable development among rural dwellers in Nigeria. It is is guided by General System Theory of Development, and highlighted the significance of self-help activities in fostering and promoting sustainable Community development. Lastly, the challenges of self-help initiative and proffer solutions to the stated challenges were discussed.